Tonal harmony : with an introduction to twentieth-century music - Kostka, Stefan M; Payne, Dorothy (New York : McGraw-Hill, 2009)
For nearly two decades Tonal Harmony has been the leading text for the two-year theory curriculum for music majors. Used at nearly 800 schools, Tonal Harmony has been consistently praised for its practicality and ease of use for student and instructor alike. The straightforward approach is supported by well-chosen examples and thoughtful exercises, and the total presentation is compatible with differing teaching styles and theoretical points of view. In addition, a set outstanding ancillaries, which include a collection of audio examples on CD (for both the text and workbook) and an extensive Instructor's Manual, round out the comprehensive teaching package
-- Part one: Fundamentals -- Elements of pitch -- Elements of rhythm -- Introduction to triads and seventh chords -- Diatonic chords in major and minor keys -- Part two: Diatonic triads -- Principles of voice leading -- Root position part writing -- Harmonic progression and the sequence -- Triads in first inversion -- Triads in second inversion -- Cadences, phrases, and periods -- Nonchord tones 1 -- Nonchord tones 2 -- Part three: Diatonic seventh chords -- The V7 chord -- The II7 and the VII7 chords -- Other diatonic seventh chords -- Part four: Chromaticism 1 -- Secondary functions 1 -- Secondary functions 2 -- Modulations using diatonic common chords -- Some other modulatory techniques -- Binary and ternary forms -- Part five: Chromaticism 2 -- Mode mixture -- The neapolitan chord -- Augmented sixth chords 1 -- Augmented sixth chords 2 -- Enharmonic spellings and enharmonic modulations -- Further elements of the harmonic vocabulary -- Tonal harmony in the late nineteenth century -- Part six: An introduction to twentieth-century music -- Materials and techniques -- Post-tonal theory -- New directions
Includes indexes
Keywords: Harmony